(untitled) (Mustansiria Dental Journal, 2024)
Aim: Different surface treatments were developed to enhance zirconia-resin cement bond strength. Conventional etching with hydrofluoric acid is not effective in enhancing bond strength, however, recent emerging acid etching formulations are thought to enhance zirconia-resin cement. The purpose of the current review is to clarify and summarize zirconia acid etching solutions that were tried to be used as a surface treatment, and to show its capability to enhance zirconia-resin cement bond strength. Materials and methods: PubMed and Google Scholar were searched for studies that investigated (zirconia etching) and (shear bond strength), and (zirconia etching solution), 11 studies were found, 6 of which matched the study criteria and were included in this review.Conclusion: highly corrosive acids in high temperature and concentrations could enhance the shear bond strength of zirconia to resin cement.